2020
DOI: 10.1002/jobm.201900511
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, antibiofilm, and antiquorum sensing activities of phytosynthesized silver nanoparticles fabricated fromMespilus germanicaextract against multidrug resistance ofKlebsiella pneumoniaeclinical strains

Abstract: The aim of the present work was to investigate the antibacterial, antibiofilm, and antiquorum sensing activities of phytosynthesized silver nanoparticles (AgNPs) fabricated from Mespilus germanica extract against multidrug‐resistant (MDR) Klebsiella pneumoniae strains. Fifty strains of K. pneumoniae were isolated from various clinical specimens. Biofilm‐forming strains were identified using Congo red agar and polymerase chain reaction (PCR) techniques. Subsequently, the antibacterial activity of phytosynthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Concerning its mechanism of action, Ts-AgNPs likely diffuse through the EPS layer of the biofilm, and induced ROS production, prompting bacterial death, and thereby reducing EPS layer formation and dissolution of the biofilms. The antibiofilm ability of Ts-AgNPs to diffuse through the EPS layer has been reported earlier [ 74 ].…”
Section: Discussionsupporting
confidence: 53%
“…Concerning its mechanism of action, Ts-AgNPs likely diffuse through the EPS layer of the biofilm, and induced ROS production, prompting bacterial death, and thereby reducing EPS layer formation and dissolution of the biofilms. The antibiofilm ability of Ts-AgNPs to diffuse through the EPS layer has been reported earlier [ 74 ].…”
Section: Discussionsupporting
confidence: 53%
“…Fourier-Transform Infrared Spectroscopy Studies. Fourier-transform infrared (FTIR) spectroscopy studies of AgNPs were made to find out the possible compounds responsible for the efficient stabilization and capping of AgNPs synthesized with M. oleifera extract [61]. The FTIR spectra of stabilized AgNPs are shown in Figure 5.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…Further, Foroohimanjili et al investigated the antibiofilm, antibacterial, and anti quorum sensing properties of phytosynthesized silver nanoparticles (AgNPs) prepared using leaf extract of Mespilus germanica against multidrug-resistant Klebsiella pneumoniae strains. Their work revealed that at sub-MIC, AgNPs prominently inhibited the establishment of biofilm in all the biofilm-producing strains (Foroohimanjili et al, 2020).…”
Section: Silver Nanoparticlesmentioning
confidence: 99%